The Life of Captain Matthew Flinders, R.N. - Scott, Ernest 1868-1939 (Cambridge library collection. Maritime exploration, 1914)
Matthew Flinders (1774–1814) joined the Royal Navy at fifteen, later claiming to have been inspired by Robinson Crusoe. He served under William Bligh, and charted the Bass Strait in 1798. In 1801 he was commissioned to chart 'New Holland', and so became the first to circumnavigate the island he referred to as Australia. After being shipwrecked on the Barrier Reef and imprisoned for six years on Mauritius on suspicion of spying, he returned to England in 1810 and began work on A Voyage to Terra Australis. He died the day after his book and maps were published. This biography, published in 1914 to mark the centenary of his death, was the first comprehensive study of this central figure of Australian maritime exploration. The leading Australian historian Ernest Scott (1868–1939) based his account on material held in private collections in France as well as on documents deposited in Australian libraries